The Effect of Service Quality and Price on Consumer Satisfaction at the Coto Makasar Nusantara Restaurant, Wayame Village, Teluk Ambon District - Musardi, Musardi; Pelamonia, Merryll; Sinay, Fransisca Riconita (CV. Rayyan Dwi Bharata, 2022)
This study aims to determine how the influence of service quality and price on consumer satisfaction at the Coto Makasar Nusantara Restaurant in Wayame Village, Teluk Ambon District. The method in this study uses a quantitative approach through the SPSS program with data collection techniques are observation, questionnaires and documentation. Based on the results of the data analysis test, it shows that simultaneously (F test) the independent variables of service quality (X1) and price (X2) together or simultaneously have a positive and significant effect on consumer satisfaction (Y) at the Coto Makasar Nusantara Restaurant, Wayame Village, Ambon Bay District. The influence of service quality and price is 65.3%, while the remaining 34.7% is influenced by other variables not examined in this study.